The Effect of Work from Home, Work Discipline on Employee Performance and Workload as a Mediating Variable at Consulates Republic of Indonesia in Tawau Malaysia - Angga Dwy Putra; Nur Damayanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Implementing Work from Home has its own challenges and constraints which are not easy, because not all areas of work can be done from home which has an impact on employee performance. Work From Home adds to the workload, lacks entertainment, and pushes oneself too much so that it can reduce motivation at work. This study aims to determine whether there is an effect of work from home and work discipline on employee performance at the Indonesian Consulate in Tawau Malaysia. This type of research is quantitative. The sampling technique used is probability sampling where the number of samples is 90 respondents. Data collection techniques by distributing questionnaires. The respondents of this study were employees of the Consulate of the Republic of Indonesia in Tawau Malaysia. Data processing is carried out using SPSS version 25. The results of this study indicate that Work from Home has a significant effect on Employees and research also shows that Workload has a significant effect on Employee Performance. This research may have some limitations, the results are limited to the effect of workload and WFH on employee performance while at the Indonesian Consulate in Tawau, Malaysia. Further research can be carried out by collecting data using a quantitative or qualitative research approach to certain respondents with different backgrounds.